In Education and in Work: The Globalized Community College - Levin, John S. (Canadian Journal of Higher Education, 2002)
This is a multiple case study of seven colleges using field methods research to examine institutional life and organizational context. This study determines that community colleges in both Canada and the United States exhibited educational and work behaviors in the 1990s consistent with the globalization process. Education was oriented to the marketplace, and the needs of business and industry received high priority in educational programming. Work within these institutions was valued for and carried out with economic ends: to realize productivity and efficiency.